The dynamic methodology of the Qur'anic exegesis between originality and renewal = المنهج الحركي في تفسير القرآن بين الأصالة والتجديد - Hussin, Haziyah; Solihin, Sohirin Mohammad (Department of al-Qur'an and al-Hadith, Academy of Islamic Studies, University of Malaya, 2012)
Manhaj al-harakī or dynamic methodology is one of modern methods or approaches in Qur’ānic exegesis which has been introduced in the early decades of the twentieth century. The development of this method has been established by Islamic movements especially Muslim Brotherhood (al-Ikhwān al- Muslimīn). However, this method has not been widely known, in fact, a few scholars of the Qur’ānic studies discussed it. This study, therefore, attempts to introduce the concept of Manhaj alharakī and its origin, as well as the dimension of renewal (tajdīd) in interpretation of the Qur’ān. By applying qualitative method and descriptive analysis, this study concludes that the Manhaj al-harakī is not completely a new method in the Qur’ānic exegesis, but it is a rebranding to the method which had been used by the Prophet Muhammad (pbuh), his companions and generation of Salaf in dealing with the Qur’ān. The application of Manhaj al-harakī in interpretation of the Qur’ān aims to bring modern Muslims closer to the Qur’ān and to understand the objective of its revelation as a practical and realistic book which deals with every aspect of human life.